1988
DOI: 10.1209/0295-5075/6/1/007
|View full text |Cite
|
Sign up to set email alerts
|

A Pressure-Induced Incommensurate Phase in Ammonium Hydrogen Oxalate Hemihydrate

Abstract: We report evidence for the existence of a new incommensurate phase in a crystal of ammonium hydrogen oxalate hemihydrate. This phase is remarkable in two aspects: it exists only above a critical pressure P,, and the incommensurate wave vector, which is parallel to the vector e* of the reciprocal lattice, has the largest variation ever reported, varying continuously from 0.147c* at 4.3 kbar to -0.25c* at the maximum pressure (8 kbar) used to date. This letter reports results of a collaborative research, perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…A new phase, called phase III, has been discovered, phase which exists only above the pressure (Py ) and below the temperature ( TY ) of a triple point, the coordinates of which are different for AHO and AHOD. Phase III has been later identified as an incommensurate phase [6] and the analysis of our data suggests a possible mechanism for its existence. Consequently, the present paper is divided as follows.…”
mentioning
confidence: 59%
See 3 more Smart Citations
“…A new phase, called phase III, has been discovered, phase which exists only above the pressure (Py ) and below the temperature ( TY ) of a triple point, the coordinates of which are different for AHO and AHOD. Phase III has been later identified as an incommensurate phase [6] and the analysis of our data suggests a possible mechanism for its existence. Consequently, the present paper is divided as follows.…”
mentioning
confidence: 59%
“…It was proposed that phase III would be an incommensurate phase, characterized by a wave vector qo which remains parallel to a given direction qo, but with a modulus varying strongly with pressure and not with temperature. This interpretation was confirmed by a neutron elastic experiment [6] which showed that qo was parallel to the cristallographic axis The two low frequencies modes of figure 4 were then found to be two acoustic phonons with wave vector qo, which are detected in the incommensurate phase through their coupling with the frozen-in modulation. Using the elastic data of I, these acoustic branches were identified as the LA mode (upper branch) and the TA mode, b polarized (lower branch of Fig.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…This suggestion was confirmed by X ray [8] and elastic neutron experiments [9] : qo was found to remain parallel to c* and to vary, for AHOD, from at most 0.06 c* at P = 2.8 kbar to at least 0.24 c* at 8 kbar.…”
mentioning
confidence: 56%